SEKULARISME DAN PENGARUHNYA DALAM DUNIA PENDIDIKAN ISLAM - Muhammad Khailid; Katimin Katimin; Zainul Fuad (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
One of the principle of secularism in education is split between the education of the mind (intellect) and the spiritual (spiritual). In fact, man created God-not-as fragmented. Man is a perfect unity, not separated spiritual from the physical, and the physical is not separated from the spiritual. When education is separate from religious instructions then there is spiritual drought in some indecision on the part of students and others. One of the rationale that underlies the spirit of secularization of education in Islamic countries is, to advance civilization in Muslim countries by means of separate education system of